Roughness integration across fingers within compared with across the hands - Roberta D. Roberts (Scientific Reports)
Abstract Feeling a texture typically involves sliding the fingers of a hand across that surface or rubbing the surface between the thumb and another digit. Texture signals appear to be integrated across the digits of a hand with perceived roughness at one finger swayed in the direction of texture touched by another finger of the same hand. To date, one study has reported similar integrative effects when the pairs of digits belong to different hands. This contrasts with observations from studies of tactile detection and tactile attention where the patterns of interactions between the digits depend on whether the digits belong to the same hand or not. The present experiments revisit the question of hand identity on multidigit roughness perception using two interval forced choice (2IFC) discrimination and single interval absolute magnitude estimation (AME). Pairs of tactile gratings were actively touched using the thumb and index fingers from the same or different hands. Attention was directed towards roughness at the thumb and index finger sensations were to be ignored. For both discrimination and ratings tasks, roughness perceived at the thumb varied with the textures touched by the index finger suggesting integration of roughness cues from the two digits. This integration occurred despite differences in the two tasks such as working memory requirements. Notably, roughness signals were integrated when originating in pairs of digits on the same hand but not when from different hands. These findings add to a body of evidence based on experiments using different stimuli and tasks, suggesting that hand identity affects interactions across the digits.